Morocco : 2018 Request for an Arrangement Under the Precautionary and Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Morocco. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
Following the expiration of the third Precautionary and Liquidity Line (PLL) arrangement, in July 2018, the authorities have requested a new PLL arrangement. They did not draw on the last three arrangements and have made further progress in reducing domestic vulnerabilities in recent years, despite a sharp pick up in oil prices. In an external environment that remains subject to important downside risks, a successor arrangement will support the authorities' policies to strengthen the economy's resilience and promote higher and more inclusive growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet